The Design of an Autoguide System Prototyped for Conventional Vehicle on Highway - Ahmad Yusof bin Nazlan, Ahmad Yusof (Universiti Teknologi Petronas, 2010)
Accident problem is a one of the big issue in this country. From the statistic made by Jabatan Keselamatan Jalan Raya Malaysia, the accidents tragedy in Malaysia increase by year. Conventional Vehicle (heavy vehicle) is the top ranking for the numbers of accident happen in Malaysia. Neglect the human factors identified as major causes of heavy vehicle accidents in the PLUS highway in 2007. Based on the research by Department of Traffic Safety PLUS also, 38 percent of heavy vehicle accident caused by driver drowsiness, while 33.4 percent involved drivers who were driving too fast. 14 percent of accidents were attributed to the driver lost control of their vehicles. 14.6 percent were caused by technical problems such as brake failures and tire burst or monasteries. Most of the accident causes is because of the driver. So, the topic has chosen for the final year project ‘The Design of an Autoguide System Prototyped for Conventional Vehicle on highway’ is to replace the driver to control the direction and speed of vehicle. When this system applied to the conventional vehicle, it may reduce the number of accident causes by driver itself. The main steps to build the autoguide prototyped are start with study of literature review. This help to choose the suitable hardware and software such as sensor. After that, design the circuit for the prototyped and programmed the peripheral interface controller (PIC) by using CCompiler. Then, build the complete prototyped and followed by testing the prototyped at the track that build before. This prototyped used PIC16F877A microcontroller as its brain and receive input from ultrasonic sensor(SRF04) at front and side of prototyped. Front sensor while detect the obstacle at front to control the speed and side sensor will detect the wall of track to control the direction or position of prototyped. The prototyped that has developed is to prove about the autoguide system. This can show how the system work and the material needed in order to build the real product of autoguide system in real life.